Tracing the Legal Consequences of Refusing Covid-19 Vaccinations - Suleman Ibrahim (Universitas Negeri Gorontalo, 2019)
This study is intended to find out how the legal impact of the rejection of the vaccination policy by the people of Gorontalo. The type of research used is normative-empirical legal research. Namely, research that focuses on the existence of the mandate of legal norms (laws and regulations) with facts or patterns that exist in the field. While the approach used is a statutory approach and a case approach. The data sources used are primary data sources as the main data and secondary data sources as supporting data consisting of documents and scientific works related to the problems being discussed. The results show that the legal impact of refusing the vaccination policy by the public is the existence of administrative sanctions, sanctions, fines, and criminal sanctions for those who refuse the implementation of the Covid-19 vaccination policy, as specified in the legislation.Keywords: Legal impact; Policy; Covid-19 Vaccination